ANALISIS NUMERIC HAMBATAN KAPAL KATAMARAN DENGAN VARIASI JUMLAH DAN SUDUT STEPPED HULL - Muhammad Syauqi (2023)
Stepped hull is a modification of the ship's hull which has the principle of reducing the wet surface so as to make resistance smaller. This hull modification is still rarely used, although stepped hull hull modifications have proven their effectiveness. The purpose of this study was to find the effect of the number and angle of the step hull on the drag on the catamaran. This study uses CFD and there are 7 ship models used to compare the simulation results. The variations of the ship model used are V0 0step 0°, V1 1step 180°, V2 2step 180°, V3 1step 90°, V4 2step 90°, V5 1step 90° Demihull CL, and V6 2step 90° Demihull CL. The results obtained in this study prove that the use of a stepped hull can reduce the resistance received by the catamaran hull. However, this depends on the number of steps and the angle used where V2 which uses 2 steps with an angle of 180° experiences an additional resistance of 11% due to the appendage, and V5 which uses 1 step with an angle of 90° which is centered on Demihull CL gets a reduction in resistance of - 20%. From the research conducted, it can be said that to use a stepped hull on a catamaran, the number factor and step angle must be considered, this can determine the effectiveness of the stepped hull used and produce different resistance reductions.